PENGARUH YOR DAN TOTAL BOR TERHADAP KINERJA OPERASIONAL PADA PT PELINDO III (PERSERO) TERMINAL PETIKEMAS SEMARANG - Dhela Novita Anggrahini; Karnowahadi - Karnowahadi; Paniya - Paniya (Politeknik Negeri Semarang, 2018)
This research aims to analyze the influence of total Yard Occupancy Ratio (YOR) and Total Berth Occupancy Ratio (BOR) on the operational performance at PT PELINDO III (Persero) Semarang Container Terminal. The technique of analysis used is multiple linear regression conducted with the Ordinary Least Square (OLS) test methods and Goodness of Fit Test. This research uses obtained secondary data from Semarang Container Terminal such as monthly report of the total Yard Occupancy Ratio (YOR), monthly report of total Berth Occupancy Ratio (BOR) and monthly report of operational performance. Based on the research that had been done, there is one significant factor with a significance level ???? = 0.05, either simultaneously or partially on the operational performance in Semarang Container Terminal, namely total Berth Occupancy Ratio (BOR). The results of F-test, shows that F sig. value about (0.000) < significance level (α = 0.05), it means that Total Yard Occupancy Ratio (YOR) and Total Occupancy Ratio (BOR) has significant affect on the operational performance at Semarang Container Terminal. Based on the result of t-test, partial total Berth Occupancy Ratio (BOR) has significant positive effect on the operational performance at Semarang Container Terminal with sig. value about 0.000 < ???? = 0.05 sig. Level and the coefficienct of 560,687 and the total Yard Occupancy Ratio (YOR) didn’t significantly affect on the operational performance at Semarang Container Terminal because it had a significant value (0.457) > sig. Level (???? = 0.05). While the Determination Coefficient (Adjusted R2) = 0.578 or 57.8%, it means that the operational performance at Semarang Container Terminal was 57,8% which was explained by Yard Occupancy Ratio (YOR) and Berth Occupancy Ratio (BOR). The rest of 42.2% were affected by any other factors outside the model.